Pengaruh Metode Latihan Time Control Speed Strength dan Plyometric Terhadap Peningkatan Daya Ledak Otot Pada Atlet Lompat Jauh PPLP Jawa Barat - Nida Nabilla (JUARA : Jurnal Olahraga, 2025)
This thesis is based on the author's observation of one of the supporting factors in long jump sports, which is the explosive power of the leg muscles. This sport requires optimal explosive power of the leg muscles to achieve the best jumping results. The purpose of this study is to determine the influence of the Time Control Speed Strength (TCSSM) training method and the plyometric training method, as well as the differences between these two methods, on the improvement of leg muscle explosive power in the long jump athletes of PPLP West Java. The research method used in this study is the Two Group Pretest-Posttest Design experiment. The sample consists of 8 long jump athletes from PPLP West Java, selected using the total sampling technique and divided into two groups: the TCSSM group and the plyometric group. The instrument used in this study is the standing broad jump test. Based on the data processing and analysis, both TCSSM and plyometric training methods have a significant influence on the improvement of lower leg explosive power in the long jump athletes of PPLP West Java. However, considering the overall study, the plyometric training method showed better results in improving leg muscle explosive power in long jump athletes. Therefore, it can be concluded that the plyometric training method has a more significant impact compared to the Time Control Speed Strength training method on the improvement of leg muscle explosive power in the long jump athletes of PPLP West Java. The author suggests further research on plyometric training to enhance leg muscle explosive power using different methods or systems within plyometric training, based on what the researcher has already explored regarding its effects on enhancing leg muscle explosive power.